GEOMETRIC PRACTIES IN CULTURAL CONTEXTS: AN ETHNOMATHEMATICAL ANALYSIS OF THE KEBUMEN WAYANG KAYON - Rahmawati, Dewi; Kusuma, Anggun Badu (Program Studi Magister Pendidikan Matematika, Universitas Siliwangi, 2026)
Mathematics is not only manifested as a formal symbolic system but also develops as a form of thinking embedded in cultural practices. This study aims to analyze the mathematical elements of the kayon (gunungan) in Kebumen shadow puppetry as representations of mathematical practices and to examine their relevance for geometry education. A qualitative interpretative approach within the framework of ethnomathematics was employed using an emic–etic perspective. Data were collected through visual observation, semi-structured interviews with a puppeteer-craftsman, and documentation supported by relevant literature. The data were analyzed thematically and interpretatively by linking cultural practices with formal mathematical concepts. The findings reveal that the triangular structure, reflective symmetry, repetitive ornament patterns, and height–width proportions of the kayon function as practical mechanisms for achieving aesthetic balance and functional stability rather than merely as visual forms. These results demonstrate that non-formal mathematical knowledge possesses epistemological legitimacy within its cultural context. This study contributes to the theoretical development of ethnomathematics by repositioning cultural artifacts as representations of mathematical practices and provides a conceptual foundation for culturally responsive geometry learning.